Water conservation in garment bleaching using aerosol technology. Issue 23 (December 2022) - Wahab, Abdul; Hussain, Tanveer; Ashraf, Munir
Bleaching is one of the most highly polluting textile wet processes. High water and chemical consumption, and high volume of the resulting effluent, have huge implications for the environment. In this study, an aerosol process has been compared with the conventional process for bleaching of textile socks. In the conventional bleaching process, socks are immersed into a rotating drum filled with water to ensure uniform application of chemicals, while in the aerosol bleaching process, compressed air was mixed with the chemical solution to generate a cloud of bleaching reagents inside the rotating drum of the exhaust processing machine, using the minimum amount of water. The results show comparable whiteness results of the bleached socks, with up to 75% water saved in the aerosol beaching process as compared to the conventional bleaching process. Due to lower water consumption, the overall chemical consumption is also significantly reduced. Citric acid and silicone softener consumption of the process were reduced by 28% and 60%, respectively. The aerosol technology can be retrofitted on existing conventional machines with minimal initial investment and shows immense potential for reduction in water and chemical consumption and harmful impacts on the environment. This study aimed to align developments in the textile and apparel industry with sustainable development goals #6, 12, and 14, which are clean water and sanitation, responsible consumption and production, and life below water, respectively.